Biofilms, Coagulase Negative Staphylococci And The Saga Of Catheter Related Bloodstream Infections. - DR. CHANDAN KUMAR SHAW,; DR. PRACHI SHAW., (International Journal of Pharma and Bio Sciences, 2012)
Catheter related bloodstream infections are a major problem in most tertiary care hospitals. Among the various organisms associated with nosocomial infections, coagulase negative staphylococci are responsible for majority of the catheter related infections. They are usually resistant to standard antibiotics necessitating prolonged hospital stay and amplifying the cost of treatment manifold which usually becomes a vicious cycle difficult to break and ultimately contributing to increased morbidity and mortality. Coagulase negative staphylococci are skin commensals but the strains producing biofilms manage to evade the host immune system. Biofilms consist of a microbially derived sessile community characterized by cells that are irreversibly attached to a substratum or each other, embedded in a matrix of extracellular polymeric substances, exhibiting an altered phenotype with respect to growth rate and gene transcription. This unnatural yet favourable ecological niche protects the organisms from host immune responses and antimicrobials. In the following account we present the characteristics of biofilms and the latter’s relationship with catheter related blood stream infections particularly by coagulase negative staphylococcus and vice versa. Together, biofilms and coagulase negative staphylococci dominate the saga of catheter related sepsis and strict asepsis protocols related to catheter placement and maintenance and rational antibiotic policy are the only hope as other approaches to inhibition of biofilm formation are still experimental.